Some nonlinear mechanical problems solved with analytical solutions - Filipich, Carlos Pedro (2004)
In this paper the analytical solution of nonlinear ordinary differential systems is addressed. Some of the problems are classical in the related literature and exhibit chaotic behavior in certain ranges of the involved parameters despite being simple-looking deterministic systems. The solutions are approached by means of the old technique of power series to solve ordinary differential equations. The independent variable is time in all the illustrations and elementary recurrence algorithms are obtained. This is an alternative to the standard numerical techniques and ensures the theoretical exactness of the response. Several examples are included and trajectories diagrams, phase plots, etc. are shown. The desired numerical precision is attained using time steps several times larger than the usual ones. The availability of an analytical solution may be an additional tool within a standard qualitative analysis. The solution of higher order problems and governed by partial differential equations is under study.